On the influence of magnetic topology on the propagation of internal gravity waves in the solar atmosphere. (8th February 2021) - Vigeesh, G.; Roth, M.; Steiner, O.; Fleck, B.
Abstract : The solar surface is a continuous source of internal gravity waves (IGWs). IGWs are believed to supply the bulk of the wave energy for the lower solar atmosphere, but their existence and role for the energy balance of the upper layers is still unclear, largely due to the lack of knowledge about the influence of the Sun's magnetic fields on their propagation. In this work, we look at naturally excited IGWs in realistic models of the solar atmosphere and study the effect of different magnetic field topographies on their propagation. We carry out radiation-magnetohydrodynamic simulations of a magnetic field free and two magnetic models—one with an initial, homogeneous, vertical field of 100 G magnetic flux density and one with an initial horizontal field of 100 G flux density. The propagation properties of IGWs are studied by examining the phase-difference and coherence spectra in the k h  −  ω diagnostic diagram. We find that IGWs in the upper solar atmosphere show upward propagation in the model with predominantly horizontal field similar to the model without magnetic field. In contrast to that the model with predominantly vertical fields show downward propagation. This crucial difference in the propagation direction is also revealed in the difference in energy transported by waves for heights below 0.8 Mm. Higher up, the propagation properties show a peculiar behaviour, which require further study. Our analysis suggests that IGWs may play a significant role in the heating of the chromospheric layers of the internetwork region where horizontal fields are thought to be prevalent. This article is part of the Theo Murphy meeting issue 'High-resolution wave dynamics in the lower solar atmosphere'.